Contributions of hemicellulose, cellulose and lignin to the mass and the porous properties of chars and steam activated carbons from various lignocellulosic precursors - Cagnon, B.; Py, X.; Guillot, A.; Stoeckli, F.; Chambat, G.
In this study, contributions of hemicellulose, cellulose and lignin to the mass and the porous properties of chars and activated carbons from various lignocellulosic materials were studied. A predictive calculation was established using the experimental results obtained for the three components separately to evaluate the carbonization and activation yields and their respective contributions to the chars and to the subsequent activated carbons of various precursors in term of weight fraction. These equations were validated. The results showed that lignin can be considering as being the major contributor of all chars and activated carbons. Besides, the evolution of the mean pore size versus the specific porous volume showed that each component contributes to the porosity of chars and activated carbons whatever is its weight contribution.
Keywords: ACTIVATED CARBON; ACTIVATION; HEMICELLULOSE; CELLULOSE; LIGNIN